Pkm Community health canteen partnership program partners with SMPN 1 and 2 Porong Sidoarjo - Hanum, Sri Mukhodim Faridah; Latifah, Fitri Nur (Universitas Nusantara PGRI Kediri, 2019)
Community health canteen partnership program partners with SMPN 1 and 2 Porong Sidoarjo has a goal of empowering healthy canteen. Given the importance of canteen role, then canteen management should get more attention from school managers and local government. Both partners are selected because they have problems that must be addressed for the improvement of canteen management according to the standard. The problems faced by partners such as there are still many types of foods sold contain dyes, flavorings, preservatives, and thickener. Some foods are packed without immaculate and hygienic covers/wrappers, even though it has been displayed at storefront for storing food. Hot food containers with plastic cups and large food wrappers are mostly still using plastics that are not environmentally friendly. Solutions are provided by conducting training in order to increase the school's citizens understanding of healthy food choices. School canteen development is in accordance with MOH RI standards, thus the goals of healthy canteen program by the government can be achieved, that is to reduce snack poisoning, to reduce the usage of non-qualified food additives, to reduce the packaging of food and beverages from plastic materials. Implementation. After that, it provides assistance to the partners of PKM so that results can be implemented properly. The results of community service show that there is a positive influence on the partner environment which is shown by the change of sellers’ behavior to provide healthy and nutritious food and also not using the food containers that are made from hazardous materials for health. In managing healthy school canteen, it is developed to become healthy canteen according to government standard.